2008
DOI: 10.1097/chi.0b013e3181886eab
|View full text |Cite
|
Sign up to set email alerts
|

Subthreshold Symptoms of Depression in Preadolescent Girls Are Stable and Predictive of Depressive Disorders

Abstract: Objective-Given the risk for adolescent depression in girls to lead to a chronic course of mental illness, prevention of initial onset could have a large impact on reducing chronicity. If symptoms of depression that emerge during childhood were stable and predictive of later depressive disorders and impairment, then secondary prevention of initial onset of depressive disorders would be possible.Method-Drawing from the Pittsburgh Girls Study, an existing longitudinal study, 232 nine-yearold girls were recruited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
90
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(99 citation statements)
references
References 41 publications
6
90
1
2
Order By: Relevance
“…Still, studies of late adolescence Fergusson et al, 2005;Shankman et al, 2009;Lewinsohn et al, 2000) produce results similar to the adult studies, and population-based taxometric analyses suggest that depression may be viewed dimensionally also in children and adolescents (Hankin et al, 2005). Recent studies suggest that childhood and adolescent SD is associated with severe impairment (Keenan et al, 2008;Gonzalez-Tejera et al, 2005), and with future risk of developing MDD (Rohde et al, 2009;Johnson et al, 2009) similar to findings in adult populations. Hence, if SD in children and adolescents is a precursor to MDD, it would be an obvious target for indicated preventive intervention (aimed at individuals with subthreshold symptoms) (Munoz et al, 2010).…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations
“…Still, studies of late adolescence Fergusson et al, 2005;Shankman et al, 2009;Lewinsohn et al, 2000) produce results similar to the adult studies, and population-based taxometric analyses suggest that depression may be viewed dimensionally also in children and adolescents (Hankin et al, 2005). Recent studies suggest that childhood and adolescent SD is associated with severe impairment (Keenan et al, 2008;Gonzalez-Tejera et al, 2005), and with future risk of developing MDD (Rohde et al, 2009;Johnson et al, 2009) similar to findings in adult populations. Hence, if SD in children and adolescents is a precursor to MDD, it would be an obvious target for indicated preventive intervention (aimed at individuals with subthreshold symptoms) (Munoz et al, 2010).…”
Section: Introductionmentioning
confidence: 76%
“…The three studies examining impairment as an outcome of SD all found it to be enhanced (Johnson et al, 2009;Oldehinkel et al, 1999;Keenan et al, 2008). Johnson et al (2009) found that SD in adolescence was associated with clinical impairment at age 33 (Johnson et al, 2009).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Some of our adolescent sample (8 of 29), described changes occurring a year or more prior to the onset of MDD. Some prospective studies in children and adolescents show that the presence of depressive symptoms at a given time point is associated with the onset of MDD a year or more afterwards [24,25,26]. Our results demonstrate that in some participants, these symptoms may be prodromal to depression rather than a resolved episode that is a risk factor for later depression or a pre-existing vulnerability.…”
Section: Discussionmentioning
confidence: 55%